Effectiveness of Microfinance Policy in Nigeria, 2010-2017 - Eko-Raphaels, M U.; Osadume C. R (Journal of Economics and Sustainable Development, 2020)
This study evaluates the effectiveness of microfinance policy in Nigeria from 2010 to 2017. The Study used AMJU Microfinance Bank as its sample and the objectives of the study are to examine appropriate client targeting mechanisms that enhance good microfinance practice aimed at poverty reduction and how client impact evaluation improves operational efficiency and effectiveness. Propensity Score Matching (PSM) technique of micro econometric framework was used to establish the counterfactual for participants. The fundamental evaluation problem of selection bias was treated in the study and primary data obtained through interviews were analysed. The findings show that microfinance client exist rate was on the increase for established clients being significant; and client loan size dissatisfaction for older clients was on the rise and customers that have benefited from micro credits were better-off than non-beneficiaries. The study concludes that Microfinance is effective in poverty reduction and recommends amongst others that the delivery methodology should be tailored after their operational strategy and target clients; and also, appropriate feedback mechanism be built into their product and services delivery to encourage impact evaluation of participants’ responses, thereby, providing relevant inputs for the formulation of effective National Microfinance Policy in Nigeria.
This study evaluates the effectiveness of microfinance policy in Nigeria from 2010 to 2017. The Study used AMJU Microfinance Bank as its sample and the objectives of the study are to examine appropriate client targeting mechanisms that enhance good microfinance practice aimed at poverty reduction and how client impact evaluation improves operational efficiency and effectiveness.
Keywords: Microfinance; National Microfinance Policy; Financial Services; Financial Development